Cardboard Media as an Innovation in Solfegio Learning: a Creative Solution Amidst the Limitations of Dayak Musical Instrument - Sagala, Mastri Dihita (Yayasan Keluarga Guru Mandiri, 2026)
Limited access to the Dayak traditional musical instrument, the Dau’, is driving innovation in music education in the digital age. This research explores students' perceptions of using cardboard media as a creative alternative in learning the fundamentals of instruments. Through a qualitative approach, this study found that students responded positively to cardboard media. Data was collected through participant observation, documentation, and interviews with 2023 Performing Arts Education students at Tanjungpura University. Open-ended questions are used to understand how students perceive the cardboard media used in the learning process. Data analysis used triangulation to understand students' opinions on learning media. The research findings indicate that students have a positive view of using cardboard media in basic Dayak music learning. They assess that this media is not only effective in facilitating understanding of Dayak music concepts but also stimulates creativity and fine motor skills. This finding suggests that cardboard media can be an innovative and flexible solution in traditional music education, especially in resource-limited environments. The implications of this research open up opportunities for further development, such as integrating augmented reality technology, to create a more immersive and engaging learning experience for millennials.